2012
DOI: 10.1103/physrevb.86.104201
|View full text |Cite
|
Sign up to set email alerts
|

Probing defects in Al-Mg-Si alloys using muon spin relaxation

Abstract: Muon spin methods are very sensitive to nanoscale defects such as trace elements and vacancies in metals. This sensitivity is required when investigating Al-Mg-Si alloys, a complicated system in which diffusion-controlled phase transformations are responsible for the most important hardening mechanisms. We present muon spin relaxation experiments conducted on Al-Mg-Si alloys at measurement temperatures in the range 20-300 K. Varying the alloy composition and heat treatment, we find differences in muon depolari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Proc. , 011030 (2018)Carlo simulation, in which four variable parameters were employed: the dipolar width , trapping rate  t , detrapping rate  d , and the fraction of initially trapped muons P 0 , following our previous procedure [7]. This method has been introduced in the literature [13,14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proc. , 011030 (2018)Carlo simulation, in which four variable parameters were employed: the dipolar width , trapping rate  t , detrapping rate  d , and the fraction of initially trapped muons P 0 , following our previous procedure [7]. This method has been introduced in the literature [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have successfully studied heat treatment effects on the Mg/Si/vacancy clusters in Al-Mg-Si (6000 series) alloys by the zero-field muon spin relaxation spectroscopy [7][8][9][10]. Al-Mg-Si alloys are known to be quite sensitive to the aging process, including natural aging (stored at room temperature).…”
Section: Introductionmentioning
confidence: 99%
“…The observed muon spin relaxation functions give us rich information on muon hopping between defects in Al alloys. Our recent work with Al-Mg-Si, Al-0.5%Mg, and Al-0.5%Si alloys has demonstrated that the muon trapping rates depended on the heat treatment and solute concentrations: 1) the concentration of dissolved Mg dominates the ν t values at lower temperatures, 2) the ν t values around 200 K reflect a number of clusters and vacancies, 3) a natural aging (alloys are stored at room temperature) effect is clearly observed with Al-0.5%Si [12][13][14][15]. This contribution will review recent experimental results of muon spin relaxation versus temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[37] Timedependent magnetization [92] and muon measurements have also been used recently. [93,94] 4. Direct Characterization of Clusters À Atom Probe Tomography…”
Section: Other Techniquesmentioning
confidence: 99%